2007
DOI: 10.1111/j.1365-2702.2006.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the experimental design capture the effects of complementary therapy? A study using reflexology for patients undergoing coronary artery bypass graft surgery

Abstract: It is suggested that reflexology should be tailored to individual needs and research methods used that allow for capturing its holistic nature. Further scholarly work is warranted to explore several methodological issues in studying complementary therapies in a highly complex treatment situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 22 publications
(47 reference statements)
3
33
0
Order By: Relevance
“…The study by Shiow-Luan Tsay on gastrointestinal cancer patients as well as the research by Kahangi et al examining the effect of feet reflexology on level of anxiety before coronary artery bypass grafting surgery on 50 volunteer patients confirms this result [29,30]. In the research by Briony et al, reflexology was also an effective method to mitigate stress, with the reduction being significant between the two groups [26].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The study by Shiow-Luan Tsay on gastrointestinal cancer patients as well as the research by Kahangi et al examining the effect of feet reflexology on level of anxiety before coronary artery bypass grafting surgery on 50 volunteer patients confirms this result [29,30]. In the research by Briony et al, reflexology was also an effective method to mitigate stress, with the reduction being significant between the two groups [26].…”
Section: Discussionsupporting
confidence: 60%
“…The people in the treatment group underwent reflexology for 30 min, while the control individuals rested during these 30 min. Anxiety and physiological variables were measured before and after reflexology sessions once per day for more than 5 days [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] In addition, Gunnarsdottir and Jonsdottir et al did not show any significant changes in other physiological parameters after reflexology massage in patients with chronic heart failure except the reduction of SBP. [39] In five clinical trials, Wang reported some effects of reflexology compared to general massage. [40] Such differences in results can be attributed to different techniques and reflexology spots on hands.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that neuroimaging could be used to examine the basis of reflexological effects (Nakamaru et al, 2008). Reflexotherapy is a complementary method that relaxes and reduces stress (Gunnarsdottir & Jonsdottir, 2007).…”
Section: Introductionmentioning
confidence: 99%